Inovasi Jaringan Pelayanan Bagi Penyandang Disabilitas (Jalan Pintas) di Dinas Kependudukan dan Pencatatan Sipil, Kabupaten Pasuruan - Riberu, Maria Gabriella; Wulandary, Roro Merry Chornelia; Ra'is, Dekki Umamur (Yayasan Lentera Avanya Nagari, 2024)
Administrative services in Indonesia are still an issue that needs comprehensive attention and resolution. There is still discrimination in public service practices for vulnerable groups of persons with disabilities. Therefore, public service providers must be based on social justice without discriminatory elements. As stated in Law Number 25 of 2009 concerning public services which is a breath of fresh air in efforts to provide good public services. So innovation is needed which is the main need as an answer to the various problems that are being faced. This study aims to find out the innovation of